In the family way : a novel - Becker, Laney Katz (HarperCollins Publishers, 2025)
"A novel in the vein of Lessons in Chemistry and Big Little Lies, about the friendship between a group of suburban housewives and a teenage unwed mother as they navigate their pregnancies-both wanted and unwanted-in a time when abortion is illegal and before the women's movement has taken flight. Think of a time-maybe not so long ago!-when women's rights were in question. 1965, "middle America": Abortion is illegal, divorce is shameful, and women can't even get their own bank accounts or sign their own leases. In this novel, a group of women grapple with the issues of the day-and with their own complicated feelings about being wives, mothers-and people. The story centers around a group of women who open up their suburban households to girls from the local home for unwed mothers, teenagers who have gotten themselves "in the family way"-some so naïve they don't even really understand how-and are sent to local families to help out with housework and to be, a little bit, mothered themselves. It's a six-month deal-once their due dates approach, these girls go to the hospital to give birth, they give up their babies, and they have agreed never to contact their "host families" again. Obviously, this gets complicated when real people are involved, and the people here are real and complicated: a woman who desperately wants, and keeps losing, babies, the wife of a nice Jewish doctor who is so squeamish and prudish she barely knows more than the pregnant fifteen-year-old who comes to live with her, and her sister, who's married to the proverbial nice Jewish lawyer who, she discovers in the worst way, is very very much the opposite of the man of her dreams. Part Big Little Lies and part Little Fires Everywhere, this debut novel from beloved literary agent Laney Katz Becker is all heart (plus history!). It is one of the rare novels that both chronicles the lives of women who came of age in the 1960s AND has something to teach (in the most un-teachy way) the women who've come after them"--